A strategy and roles for urban planning in fostering sustainable happiness - Miller, Donald (2014)
The human dimension of sustainability – the balance of planet, people, and prosperity concerns – importantly includes wellbeing that is the means to the end of happiness. This paper explores what we think that we know about happiness, possible roles of urban planning in fostering happiness, and how environmental features can be enhanced by planning and so contribute to the happiness of a city’s residents and visitors. Recent developments in positive psychology provide a basis for this inquiry, and are reviewed. A focus of this paper is on The Happiness Initiative in Seattle, Washington. This recent non-governmental program, begun by Sustainable Seattle, is inspired by the earlier effort in Bhutan to replace or augment Gross Domestic Product with measurement and attention to the Gross Domestic Happiness. Finally, the paper will explore how findings from research on factors contributing to happiness can be applied in urban planning.